Aspects of Weak, $s$-cs and Almost Injective Rings - Zeyada, Nasr A.; Amin, Amr K. (Sarajevo Journal of Mathematics, 2024)
It is not known whether right $CF$-rings ($FGF$-rings) are right artinian (quasi-Frobenius). This paper gives a positive answer of this question in the case of weak $CS$ ($s$-$CS$) and $GC2$ rings. Also we get some new results on almost injective rings.